Basic characteristics and accumulation mechanism of Sinian−Cambrian giant highly mature and oil-cracking gas reservoirs in the Sichuan Basin, SW China. Issue 4 (July 2018) - Luo, Bing; Yang, Yu; Zhou, Gang; Luo, Wenjun; Shan, Shujiao; Xia, Maolong
Old Mesoproterozoic−Cambrian successions have been regarded as an important frontier field for global oil and gas exploration in the 21st century. This has been confirmed by a recent natural gas exploration breakthrough in the Sinian and Cambrian strata, central Sichuan Uplift, Sichuan Basin of SW China. However, the accumulation mechanism and enrichment rule of these gases have not been well characterized. This was addressed in this work, with aims to provide important guidance for the further exploration while enriching the general studies of the oil and gas geology in the old Mesoproterozoic–Cambrian strata. Results show that the gas field in the study area is featured by old target layers (Sinian–Lower Cambrian), large burial depth (>4500 m), multiple gas-bearing intervals (the second and fourth members of the Sinian Dengying Formation and the Lower Cambrian Longwangmiao Formation), various gas reservoir types (structural type and structural–lithologic type), large scale (giant), and superimposing and ubiquitous distribution. The giant reserves could be attributed to the extensive intercalation of pervasive high quality source rocks and large-scale karst reservoirs, which enables a three-dimensional hydrocarbon migration and accumulation pattern. The origin of natural gas is oil cracking, and the three critical stages of accumulation include the formation of oil reservoirs in Triassic, the cracking of oil in Cretaceous, and the adjustment and reaccumulations in the Paleogene. The main controlling factor of oil and gas enrichment is the inherited development of large-scale stable paleo-uplift, and the high points in the eastern paleo-uplift are the favorable area for ​natural gas exploration.